Studi Implementasi Aplikasi NS5 di PT. Maritim Barito Perkasa Banjarmasin - Pramudya Darmawan; Saladin Ghalib; M. Hasanur Ariffin (JURNAL BISNIS DAN PEMBANGUNAN, 2017)
Application Deployment NS5 PT. Maritim Barito Perkasa Banjarmasin intended to determine the extent of NS5 applications can be used and what are the constraints faced by ICT PT. Maritim Barito Perkasa Banjarmasin to implement this application.The approach used method is a qualitative approach. The strategy used in this study is to outline a program NS5 by conducting in-depth interviews and document key informant associated directly with the NS5 program.The results showed that the problems that arise in the implementation of NS5 PT. Maritim Barito Perkasa is1. The human resources are still reluctant to make changes2. The new program is still considered difficult to learn.3. The need for the cost of making changesTherefore it is necessary to change the perspective of making changes and their training to the NS5 application. Changes in information systems require substantial support from the management of PT. Maritim Barito Perkasa Keywords: NS5, Implementation, Application